1889 Ohio Gen. and Local Laws 164, An Act to Amend Section 2669 of the Revised Statutes, as Amended April 22, 1885, § 1 (vol. 84) - (:unkn) unknown (My University, 1889)
The council of the city or village may provide by ordinance for licensing all exhibiters of shows or performances of any kind, not prohibited by law, hawkers, peddlers, auctioneers of horses and other animals on the highways or public grounds of the corporation, venders [sic] of gun powder and other explosives, taverns and houses of public entertainment, and hucksters in the public streets or markets, and in granting such license, may extract and receive such sum of money as it may think reasonable[.]
Keywords: TRANSFER, MANUFACTURE & STORAGE OF GUNPOWDER